Peran Zakat Baitul Maal Hidayatullah dalam Pemberdayaan Ekonomi Pesantren Tahfidz Hidayatullah di Gresik - Sudarto; Samsudin (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to analyze the role of zakat managed by Baitul Maal Hidayatullah (BMH) in the economic empowerment of Pesantren Tahfidz Hidayatullah in Gresik. The pesantren’s need to financially support its students highlights the importance of developing economic self-reliance through productive business units. This research employs a qualitative method with a case study approach, where data were collected through interviews with BMH Prodaya staff and pesantren administrators, field observations, and documentation. Data analysis was conducted using the interactive Miles and Huberman model, while data validity was ensured through source and method triangulation. The findings reveal that BMH’s productive zakat significantly contributes to strengthening the pesantren’s economy through support for its cooperative, livestock unit, aqiqah services, and the PPAS social program. The impact is reflected in increased pesantren income, reduced dependence on donations, and the creation of educational entrepreneurship experiences for students. These findings align with existing literature indicating that productive zakat can enhance institutional economic independence when managed sustainably. The discussion highlights that synergy among BMH, the pesantren, and the community is a key factor in the program’s success. However, the study has limitations related to the availability of detailed financial data and the short research duration. The study concludes that BMH’s productive zakat management has been effective in building the pesantren’s economic independence and should be further strengthened through capacity building, human resource training, and continuous monitoring